2013
DOI: 10.4161/auto.22805
|View full text |Cite
|
Sign up to set email alerts
|

Autophagy-dependent EIF2AK3 activation compromises ursolic acid-induced apoptosis through upregulation of MCL1 in MCF-7 human breast cancer cells

Abstract: (2013) Autophagy-dependent EIF2AK3 activation compromises ursolic acid-induced apoptosis through upregulation of MCL1 in MCF-7 human breast cancer cells, Autophagy, 9:2,[196][197][198][199][200][201][202][203][204][205][206][207]

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
37
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 71 publications
(40 citation statements)
references
References 33 publications
2
37
1
Order By: Relevance
“…Overexpression of Bcl‐2 inhibited the upregulation of Beclin‐1 and followed autophagosome formation in HSFBs. Our data clearly confirmed that the UA‐induced decrease in Bcl‐2 contributed to UA‐induced Beclin‐1 activation and followed autophagosome formation, which was contradictory to a previous study in MCF‐7 and U87 cells . The discrepancy in these results may be attributed to cell type variance.…”
Section: Discussionsupporting
confidence: 59%
“…Overexpression of Bcl‐2 inhibited the upregulation of Beclin‐1 and followed autophagosome formation in HSFBs. Our data clearly confirmed that the UA‐induced decrease in Bcl‐2 contributed to UA‐induced Beclin‐1 activation and followed autophagosome formation, which was contradictory to a previous study in MCF‐7 and U87 cells . The discrepancy in these results may be attributed to cell type variance.…”
Section: Discussionsupporting
confidence: 59%
“…Although some reports suggest that compounds that induce sustained eIF2␣ phosphorylation provide cytoprotection in situations of ER stress (11), other reports have shown a prolonged suppression of protein synthesis, which is incompatible with cell survival and leads to autophagy (20). Moreover, involvement of the PERK-eIF2␣ axis of ER stress in apoptotic cell death has also been well documented (40). This is consistent with our current observations and our earlier finding that triptolide treatment causes a sustained increase in the levels of phosphorylated eIF2␣ and causes autophagyassociated cell death in S2-VP10 cells (Figs.…”
Section: Discussionmentioning
confidence: 99%
“…Ursolic acid (UA), a natural pentacyclic triterpene compound (Figure 1), which is widely found in medicinal plants such as holy basil, food, and other plants, exhibits anticancer potential effect in vitro and in vivo 15. It inhibited proliferation and caused apoptosis in cells of numerous cancers, including breast cancer,16 colon cancer,17 non-small cell lung cancer,18 cervical cancer,19 multiple myeloma,20 pancreatic cancer,21 melanoma,22 and prostate cancer 23. UA has been shown to prevent CCl 4 -induced hepatotoxicity and fibrosis via Nrf2/ARE pathway 24.…”
Section: Introductionmentioning
confidence: 99%